2017
DOI: 10.18488/journal.1.2017.79.728.737
|View full text |Cite
|
Sign up to set email alerts
|

Growing Popularity of Muslim Attire: Faith or Fashion?

Abstract: Article History JEL Classification L67, M30. Muslim attire, also popularly known as -Modest Clothing‖ is a particular dressing style for the women who adhere to Islamic faith. Traditionally, this attire has been practiced by women as part of obligation to their faith. Interestingly, last decade has seen increasing popularity of the Muslim attire in all age groups of women not only as part of their religion, but also as part of their fashion statement. The prime focus of this paper is to study consumers' opi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Balikcioglu (2018) found that fashion innovativeness and opinion leadership, as well as buying impulsiveness, have a direct impact on impulse shopping behavior, although the need for uniqueness does not have a direct impact on impulse purchase behavior but does correlate to buying impulsiveness characteristics. For example, Zabeen et al (2017) observed that Muslim women are becoming more socially involved due to their education and careers. As a result, there is a high need for apparel that provides both modesty and attractiveness.…”
Section: Originality Of Opinion Leadersmentioning
confidence: 99%
“…Balikcioglu (2018) found that fashion innovativeness and opinion leadership, as well as buying impulsiveness, have a direct impact on impulse shopping behavior, although the need for uniqueness does not have a direct impact on impulse purchase behavior but does correlate to buying impulsiveness characteristics. For example, Zabeen et al (2017) observed that Muslim women are becoming more socially involved due to their education and careers. As a result, there is a high need for apparel that provides both modesty and attractiveness.…”
Section: Originality Of Opinion Leadersmentioning
confidence: 99%
“…Definitions and terms of Islamic fashion are varied and dynamic. The founder of the Islamic Fashion Design Council (Alia Khan) defines Islamic fashion as clothes “worn primarily by practicing Muslims who have committed to the Islamic principles of dressing.” In addition, Zabeen et al (2017) mentioned that Muslim attire is any clothing that follows the principle of modesty, and it can be broadly classified into head and body coverings. The head covering has been considered one of the most important identifiers of Muslim women.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many females found to practice hijab voluntarily for integrating religiosity with modern life style (Halim, 2018;Rastanti, 2017) and appealing more respect from others. Many others personally choose it for fashion reasons (Grine & Saeed, 2017;Hassan & Ara, 2020;Rita, 2017;Zabeen, Mashruba, Shams & Sultana, 2017), expression of assertiveness (Hamsad & Alosman, 2021), selfprotection (Tabassum, Afzal, & Hadi, 2021), pious identity (Sunesti, 2016), family bonding (Rahman et al, 2018), and exercising humility (Hassim, Nayan, & Ishak, 2017;Hwang & Kim, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%